Silica Supported Indium Heterogeneous Catalyst In Benzylation And Benzoylation Of Toluene - Sek, Kei Lin (2013)
Indium incorporated silica with different indium content were synthesized via a template free sol-gel method. The silica used was extracted from rice husk (RH) and the resulting catalyst was labeled as RH-xIn (x = 5, 10, 15 and 20). The catalysts were characterized by physico-chemical techniques such as FTIR, N2 adsorption (BET), powder XRD, UV-Vis, SEM, EDX, TEM and AAS for the elemental analysis. RH-blank (without indium) was synthesized as the control for the reaction. No indium was detected in the RH-blank and the percentage of indium was found increase from RH-5In to RH-20In. The N2 adsorption analysis showed the presence of type IV isotherm in RH-blank and RH-xIn, indicating the mesoporous nature of the catalysts. The XRD recorded a broad band at 2θ = 25°, which showed their amorphous character. TEM micrographs revealed the catalysts to be composed of nanoparticles. Friedel-Craft benzylation and benzoylation of toluene with benzyl chloride (BC) and benzoyl chloride (BOZ) were carried out by using RH-xIn (x= 5, 10, 15 and 20) as the catalyst. Benzylation of toluene resulted in 4-methyldiphenylmethane (4-MDM) and 2-methyldiphenylmethane (2-MDM) as the major products while disubstituted products were detected as minor product. Benzoylation of toluene gave 4- methylbenzophenone (4-MBP) and 2-methylbenzophenone (2-MBP) as major products, and 3-methylbenzophenone (3-MBP) as the minor product.